Analisis Antrian Pembuatan Mesin Pelet dengan Menggunakan Simulasi Promodel pada PT ABC - Cornellia, Riri; Oktaviani , Anggi; Widayani , Hapsari (JUDICIOUS, 2025)
In the digital era, technological development has encouraged the use of simulation as a decision-support tool in industrial production systems. PT ABC is a company operating in the machinery industry as well as in the processing of food and agricultural commodities. In its production process, the company faces difficulties in determining whether to increase or reduce pellet machine production due to the lack of accurate information regarding machine utilization rates and processing times along the production line. This study aims to analyze the queuing system and performance of the pellet machine production line using Promodel simulation to evaluate production capacity and efficiency. Simulation modeling is employed to represent the production flow and to measure key performance parameters, including processing time and machine utilization. The simulation results indicate that all machines operate within normal utilization limits (below 100%), with utilization rates of 30.11% for cutting machines, 28.03% for drilling machines, 10.03% for lathes, 26.60% for welding machines, and 5.24% for painting machines. These results suggest that the production line has not yet reached its optimal capacity. Therefore, PT ABC has the potential to increase pellet machine production without adding new machinery, provided that machine utilization, processing time, and the risk of bottlenecks along the production line are carefully considered.